Measurement of antibiotic removal efficiency of ZnO-WO3 nanocomposite and its validation through residual antimicrobial activity - Shraddha Shukla; Shashi Kant Shukla; Prashansha Singh; Himanshu Pandey; Anupam Dikshit; Avinash C. Pandey (Heliyon)
Antibiotics are very effective for treatment of infections as well as they are persistent pharmaceutical compounds, and their elimination from the water resources proved to be a major concern. Amoxicillin (AMX), Azithromycin (AZT) and Ofloxacin (OFX) are the most commonly utilized antibiotics for the treatment of infections. Each of the three antibiotics was used for the antimicrobial resistance in the current study. The mixed oxides of ZnO-WO3 were synthesized by the precipitation method by doping 10 % WO3 nanoparticles in 90 % ZnO nanoparticles. The fabricated nanocomposites were characterized by using different techniques such as UV–Vis, XRD, FTIR, SEM and TEM and the photocatalytic activity has been measured in the presence of UV-light. Further the antimicrobial residual activity (AMR) was tested to confirm the degradation of antibiotics using E. coli and Staphyllococcus aureus bacteria respectively. The characterization study revealed the presence of Zn, O and W and confirms the shape of the particle is flaky and spheroidal. The prepared ZnO-WO3 nanocomposite has been utilized for the degradation of antibiotic residues of 10 mg l−1 concentration (AMX, AZT and OFX) with different catalyst concentrations of 10 %, 20 %, 30 % and 40 %. The catalyst concentration of 40 % showed effective degradation of AMX with 89 % efficiency. AZT and OFX showed best degradation at 30 % and 10 % catalyst concentration with 90 % and 98 % efficiency respectively. Further, the AMR has been tested by the disc diffusion method and it showed huge bacterial growth at 48hrs, it was revealed that there is no antibiotic residues are left as the bacterial growth increased in the samples treated with nanocomposite and there was no bacterial growth occurs in the untreated samples. It can be concluded that the after doping with WO3 the efficiency of ZnO increased and showed better degradation of antibiotics in comparison with ZnO nanoparticle.